(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Tropical butterflies of the genus Heliconius (Nymphalidae: Heliconiini) constitute a model system for studying the genomics of speciation, mimicry evolution, and ecological adaptation, due to their spectacular wing colour pattern diversity, well-resolved phylogeny, and the availability of high-quality reference genomes for multiple species. This study investigated the genomic architecture of speciation and adaptive colour pattern divergence in four Heliconius species pairs at different stages of reproductive isolation — ranging from freely interbreeding races to fully reproductively isolated species — sampled from 28 localities across Central and South America. Whole-genome resequencing of 248 individuals (mean 15× coverage) identified 14.8 million SNPs genome-wide. Population structure analysis (PCA, ADMIXTURE) confirmed clear genetic differentiation between species pairs (FST range 0.12–0.48) with evidence of ongoing hybridisation and introgression at 6 of 28 contact zone localities. Genome scan for divergent selection identified 284 high-FST genomic windows (top 1%), strongly enriched for colour pattern loci (optix, WntA, cortex; relative enrichment 8.4× above genome background). Demographic modelling using dadi identified isolation-with-migration (IM) as the best-fit speciation model in all four species pairs, with estimated migration rates declining from 1.84 × 10-3 to 2.4 ×10-5 migrants per generation across the reproductive isolation continuum. Ancestral state reconstruction placed the origin of Heliconius mimicry in the Miocene (12.4 ± 1.8 Ma), with acceleration of wing pattern diversification rate in the Pliocene (4.8–1.2 Ma) coinciding with Andean uplift. These results advance understanding of the genetic architecture of ecological speciation and highlight colour pattern loci as the primary genomic targets of divergent selection driving Heliconius species divergence.